2014
DOI: 10.1007/s00330-014-3399-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of average glandular dose and breast cancer detection between single-view digital breast tomosynthesis (DBT) plus single-view digital mammography (DM) and two-view DM: correlation with breast thickness and density

Abstract: • DBT has higher diagnostic performance and potential to overcome limitations of DM. • Dose differences (DBT-DM, ΔAGD) were inversely correlated with breast thickness and density. • Figure of merit of MLO-DBT/CC-DM was higher than that of two-view DM. • In dense breasts, MLO-DBT/CC-DM provides better diagnostic performance with a small AGD increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
2
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 36 publications
4
30
2
4
Order By: Relevance
“…However, due to recent advances in technology, the overall AGD for a combined setting of DBT and FFDM was found similar to that of FFDM just a few years earlier on previous FFDM systems. A recent study [44] examined dose variations in 149 patients using the same type of DBT unit as in the previously described phantom-based study, and found similar results in dose-dependence of breast density and thickness. The mean AGD per acquisition for the whole study population was 6.7% higher for DBT than for FFDM, but this difference varies considerably for breasts of varying thickness and density.…”
Section: Discussionmentioning
confidence: 71%
“…However, due to recent advances in technology, the overall AGD for a combined setting of DBT and FFDM was found similar to that of FFDM just a few years earlier on previous FFDM systems. A recent study [44] examined dose variations in 149 patients using the same type of DBT unit as in the previously described phantom-based study, and found similar results in dose-dependence of breast density and thickness. The mean AGD per acquisition for the whole study population was 6.7% higher for DBT than for FFDM, but this difference varies considerably for breasts of varying thickness and density.…”
Section: Discussionmentioning
confidence: 71%
“…However, there was no significant difference between oneview DBT and FFDM alone. In another study 24 , the combination of one-view DBT and opposite-view FFDM showed better diagnostic performance than two-view FFDM in dense breasts with a small increase in average glandular dose. One-view DBT and opposite-view FFDM have also shown better lesion detection and characterization than two-view FFDM and are noninferior to two-view FFDM in cancer detection and malignant lesion characterization.…”
mentioning
confidence: 94%
“…Although a comparison is difficult, we estimated by comparing the reported graphs (AGD values vs BT) with our results that for breast thicknesses larger than 40 mm, the AGD values in our study are lower. [15][16][17] The low DBT radiation dose observed in the current study might be partially explained by the use of a step-and-shoot technique in combination with a unique DBT antiscatter grid. This antiscatter grid has a high line number and is positioned with the septa parallel to the rotation plane of the x-ray tube (parallel to the chest wall), as opposed to the orientation of conventional FFDM antiscatter grids (perpendicular to the chest wall).…”
Section: Discussionmentioning
confidence: 64%
“…On this system, radiation exposure was found to be higher for DBT compared with FFDM. [14][15][16][17] In the current study, radiation exposure of a commercially available, Food and Drug Administration (FDA)-approved DBT system was assessed in a clinical patient population. The main discerning features of this new system are the step-and-shoot technique, in which the x-ray tube stops at each angular position, combined with a dedicated antiscatter grid, with septa-oriented parallel to the chest wall, positioned on a fixed detector.…”
mentioning
confidence: 99%